Benefits of Multimodal Exercise Intervention for Postural Control and Frontal Cognitive Functions in Individuals with Alzheimer's Disease: A Controlled Trial - Andrade, Larissa P. de [UNESP]; Gobbi, Lilian T. B. [UNESP]; Coelho, Flavia G. M. [UNESP]; Christofoletti, Gustavo; Riani Costa, Jose L. [UNESP]; Stella, Florindo [UNESP] (Wiley-Blackwell, 2013)
Objective To verify the effects of a systematized multimodal exercise intervention program on frontal cognitive function, postural control, and functional capacity components of individuals with Alzheimer's disease (AD).DesignNonrandomized controlled trial with pre- and posttraining tests in a training group and a control group.SettingKinesiotherapy program for seniors with AD, SAo Paulo State University.ParticipantsConvenience sample of older adults with AD (n=30) were assigned to a training (n=14; aged 78.67.1) and a control (n=16; aged 77.06.3) group.InterventionThe intervention program was structured with the aim of simultaneously promoting better balance and frontal cognitive capacity. The participants attended a 1-hour session three times a week for 16weeks, whereas the control group did not participate in any activity during the same period.MeasurementsFrontal cognitive function was evaluated using the Montreal Cognitive Assessment, the Clock Drawing Test, the Frontal Assessment Battery, and the Symbol Search Subtest. Postural control (center of pressure area) was analyzed under four dual-task conditions. Functional capacity components were analyzed using the Timed Up and Go Test, the 30-second sit-to-stand test, the sit-and-reach test, and the Berg Functional Balance Scale.ResultsIntervention group participants showed a significant increase in frontal cognitive function (P<.001, partial (2)=0.838), with less body sway (P=.04, partial (2)=0.04) during the dual tasks, and greater functional capacity (P=.001, partial (2)=0.676) after the 16-week period.ConclusionIntervention participants performed better on dual-task activities and had better postural balance and greater functional capacity than controls.
Keywords: rehabilitation; cognition; postural control; dual task; Alzheimer's